Attenuation of neuroinflammation reverses Adriamycin-induced cognitive impairments - Allen, Barrett D. (Acta Neuropathol Commun, 2019)
Numerous clinical studies have established the debilitating neurocognitive side effects of chemotherapy in the treatment of breast cancer, often referred as chemobrain. We hypothesize that cognitive impairments are associated with elevated microglial inflammation in the brain. Thus, either elimination of microglia or restoration of microglial function could ameliorate cognitive dysfunction. Using a rodent model of chronic Adriamycin (ADR) treatment, a commonly used breast cancer chemotherapy, we evaluated two strategies to ameliorate chemobrain: 1) microglia depletion using the colony stimulating factor-1 receptor (CSF1R) inhibitor PLX5622 and 2) human induced pluripotent stem cell-derived microglia (iMG)-derived extracellular vesicle (EV) treatment. In strategy 1 mice received ADR once weekly for 4 weeks and were then administered CSF1R inhibitor (PLX5622) starting 72 h post-ADR treatment. ADR-treated animals given a normal diet exhibited significant behavioral deficits and increased microglial activation 4–6 weeks later. PLX5622-treated mice exhibited no ADR-related cognitive deficits and near complete depletion of IBA-1 and CD68(+) microglia in the brain. Cytokine and RNA sequencing analysis for inflammation pathways validated these findings. In strategy 2, 1 week after the last ADR treatment, mice received retro-orbital vein injections of iMG-EV (once weekly for 4 weeks) and 1 week later, mice underwent behavior testing. ADR-treated mice receiving EV showed nearly complete restoration of cognitive function and significant reductions in microglial activation as compared to untreated ADR mice. Our data demonstrate that ADR treatment elevates CNS inflammation that is linked to cognitive dysfunction and that attenuation of neuroinflammation reverses the adverse neurocognitive effects of chemotherapy.